2022
DOI: 10.3389/fnins.2022.917489
|View full text |Cite
|
Sign up to set email alerts
|

RNA sequencing-based identification of the regulatory mechanism of microRNAs, transcription factors, and corresponding target genes involved in vascular dementia

Abstract: Vascular dementia (VaD) is the second most common form of dementia with uncertain mechanisms and no effective treatments. microRNAs (miRNAs) and transcription factors (TFs) are considered regulatory factors of genes involved in many diseases. Therefore, this work investigated the aberrantly expressed miRNAs, TFs, corresponding target genes, and their co-regulatory networks in the cortex of rats with bilateral common carotid artery occlusion (2VO) to uncover the potential mechanism and biomarkers of VaD. Differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 81 publications
0
11
0
Order By: Relevance
“…As an in ammatory gene [45], PXN expression was upregulated after middle cerebral artery occlusion in mice, especially following 1 hour of ischemia, and the upregulation of PXN may promote in ammation and the development of acute ischemic stroke [46,47]. Besides, a sequencing result observed that PXN was notably elevated in the cortex of 2VO rats [24]. Aligned with previous studies, we found elevated levels of PXN in the hippocampus of 2VO rats and con rmed its binding relationship with miR-145-5p.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As an in ammatory gene [45], PXN expression was upregulated after middle cerebral artery occlusion in mice, especially following 1 hour of ischemia, and the upregulation of PXN may promote in ammation and the development of acute ischemic stroke [46,47]. Besides, a sequencing result observed that PXN was notably elevated in the cortex of 2VO rats [24]. Aligned with previous studies, we found elevated levels of PXN in the hippocampus of 2VO rats and con rmed its binding relationship with miR-145-5p.…”
Section: Discussionmentioning
confidence: 99%
“…Among these candidate genes, Trim2, PXN, and Nedd4l were reported to be signi cantly upregulated in the cortex of 2VO rats [24,27]. Then, the minimum free energies of binding between them and miR-145-5p were − 31.5, -35.1, and − 32.8 kcal/mol, respectively, predicted by the RNAhybrid (Fig.…”
Section: Pxn Is the Target Of Mir-145-5pmentioning
confidence: 92%
“…Studies have shown that these miRNAs may be associated with neurological diseases. For example, miR-764-3p was down-regulated in the hippocampus of rats with dementia [ 70 ]. miR-741-3p was upregulated in attention-deficit/hyperactivity disorder rats [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…After the MWM, the mice were euthanized via cervical dislocation, and the obtained samples were preserved in liquid nitrogen. The total RNA of the hippocampus was isolated with TRIzol reagent (Invitrogen, CA, United States) according to the previous protocol ( Zhao et al, 2022 ). The RNA sample used in this study was the same cohort as our reported investigation ( Cai et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%